Development of an in vitro model of calcified cerebral emboli in acute ischemic stroke for mechanical thrombectomy evaluation. (3rd January 2020) - Johnson, Sarah; McCarthy, Ray; Fahy, Brian; Mereuta, Oana Madalina; Fitzgerald, Seán; Gaudirc, Julien; Remadi, Jean-Paul; Shotar, Eimad; Sourour, Nader-Antoine; Doyle, Karen; Gilvarry, Michael; McGarry, Patrick; et al.
Abstract : ​ Background: Calcified cerebral emboli (CCEs) are a rare cause of acute ischemic stroke (AIS) and are frequently associated with poor outcomes. The presence of dense calcified material enables reliable identification of CCEs using non-contrast CT. However, recanalization rates with the available mechanical thrombectomy (MT) devices remain low. Objective: To recreate a large vessel occlusion involving a CCE using an in vitro silicone model of the intracranial vessels and to demonstrate the feasability of this model to test different endovascular strategies to recanalize an occlusion of the M1 segment of the middle cerebral artery (MCA). ​ Methods: An in vitro model was developed to evaluate different endovascular treatment approaches using contemporary devices in the M1 segment of the MCA. The in vitro model consisted of a CCE analog placed in a silicone neurovascular model. Development of an appropriate CCE analog was based on characterization of human calcified tissues that represent likely sources of CCEs. Feasibility of the model was demonstrated in a small number of MT devices using four common procedural techniques. ​ Results: CCE analogs were developed with similar mechanical behavior to that of ex vivo calcified material. The in vitro model was evaluated with various MT techniques and devices to show feasibility of the model. In this limited evaluation, the most successful retrieval approach was performed with a stent retriever combined with local aspiration through a distal access catheter, and importantly, with flow arrest and dual aspiration using a balloon guide catheter. ​ Conclusion: Characterization of calcified tissues, which are likely sources of CCEs, has shown that CCEs are considerably stiffer than thrombus. This highlights the need for a different in vitro AIS model for CCEs than those used for thromboemboli. Consequentially, an in vitro AIS model representative of a CCE occlusion in the M1 segment of the MCA has been developed.